Contemporary diagnostic imaging of diseases of the small intestine – magnetic resonance enteroclysis and enterography - Dobrowolska-Bąk, Małgorzata; Dubis, Anna; Karcz, Paulina; Rożnawska, Karolina (Nursing Problems / Problemy Pielęgniarstwa, 2019)
Examination of intestines using methods of magnetic resonance (MR) enterography and MR enteroclysis is currently considered to be the best way to visualise diseases of the small intestine like Crohn’s disease, other inflammatory diseases of the small intestine, celiac disease, small intestine tumours, and cancers. They are both used in the initial diagnostics, assessment of the severity, as well as in monitoring of the course of the disease and possible complications. Both diagnostic methods require initial preparation of the patient by oral administration of a contrast agent. There are three types of oral contrast agents used in MR enterography and MR enteroclysis: positive, negative, and biphasic. In addition, an intravenous gadolinium contrast agent is administered during the study. MR enterography and MR enteroclysis allow accurate assessment of such structures as: the thickness of the intestinal wall, layering of the intestinal wall, narrowing, obstruction, gastrointestinal fistulas, gastrointestinal adipose tissue, encapsulated or free fluid in the abdomen, and lymph nodes. The undoubted advantages of these diagnostic methods include the lack of invasiveness, the possi-bility of obtaining multifaceted images, the possibility of assessing pathology not only within the intestine, but also in parenteral localisation, and the total absence of exposure of the patient to ionising radiation. The quality of the MR images obtained using both techniques depends largely on the correct preparation of the patient before the examination, in which the nurse participates to a large extent, leading the correct cooperation of the patient with the medical staff performing the MRI examination.